Yūsuf Al-Qaraḍāwī's Thoughts on the Hadiths of Reforestation: A Maqāṣid Sharī‘ah Perspective - Kudhori, Muhammad; Faiq, Muhammad (IAIN Ponorogo, 2023)
The Qur'an states that human beings were created with a duty to prosper the earth; one of which is by preserving the environment and reforestation. This study aims to unveil the hadiths on reforestation by employing the Maqāṣid Sharī‘ah approach of Yūsuf al-Qaraḍāwī. This paper is a qualitative study with content analysis and descriptive-analytical approaches. This study found that the hadiths about the recommendation for plantation and reforestation must be interpreted generally, not restricted to certain conditions. Thus the command for reforestation applies in general, not limited to certain conditions and places. Reforestation must be carried out anywhere and anytime until the end of the day. While the proper meaning of the hadith, which contains the threat of hell for cutting down the Bidara tree, is that such a threat is addressed or people who cut down the tree in open space where it serves as a shelter for travellers and animal habitats. In addition, the hadith should also be understood to a more general meaning, particularly for the Bidara tree and all trees with the same function as shelters.